Developing a UV climatology for public health purposes using satellite data. (January 2021) - Vuilleumier, Laurent; Harris, Todd; Nenes, Athanasios; Backes, Claudine; Vernez, David
Highlights: A satellite-based UV climatology has been developed for Switzerland over 15 years. It spatial and temporal resolution are of 1.5–2 km and one hour, respectively. Its flexibility allows a large range of uses in health prevention and research. This methodology can easily be applied to most Europe and a large part of Africa. Abstract: The effects of solar ultraviolet (UV) radiation on life on Earth differ greatly. While overexposure to UV rays is harmful, small amounts of exposure are necessary for the synthesis of Vitamin D and good health. To optimize individual exposure to solar UV, it is therefore crucial to use UV data sources representative for entire populations and realistically accounting for various influencing factors. A UV climatology for Switzerland based on satellite data has been developed to provide risk estimates at population level. An algorithm generating ground-based radiation estimate has been transformed from the visible to the UV wavelength domain by adapting both a clear-sky radiation transfer model and a cloud modification factor model using satellite imagery. The algorithm allows the computation of global UV erythemal irradiance at a spatial resolution of 1.5 – 2 km and an hourly temporal resolution over fifteen years. A validation, conducted with measurements from three meteorological stations over ten years, showed that the expanded uncertainty for low hourly UVI values (UVI < 3) is about ± 0.3, while for high hourly UVI values (UVI > 6) it can go up to ± 1.5. In clear-sky situation, the uncertainty is in the range of 10–15%. The climatology developed allows to visualise potential UV exposure at regional and national scale. National prevention intervention could use new strategies to better focus on populations at risk and better tailor available researches. The UV climatology allows a high versatility in adapting the data extraction to the goal of studies using it. Further tailored data extraction and analysis will be necessary to exploit this climatology in a wide range of environmental and occupational health applications. Its development was focused on Switzerland, but the techniques used can be extended globally.